Finite element analysis on the flexural behaviour of internally pre-stressed i-beam - Effa Syarmiza, Saharudin (2015)
Many bridges will be distress after a certain life span. Larger increase in the deflection will develop and also a very deep crack may develop instantaneously if the loads are kept constant after cracking happen to the structure. Therefore, cracking and deformation characteristics of the structural members are important in design. Deterioration of the existing bridges is mainly caused by the increased in the traffic loading on those bridges, progressive structural aging of the bridges and the corrosion of the reinforcement from various causes such as the weathering condition which has become the major causes all over the world. The traffic volumes that are coming from the heavy trucks on the bridges have risen to the level that exceeds the values design at the time of the design. Therefore, many of the bridges has suffered fatigue damage from the case of heavy traffic volume and in need of urgent repair and strengthening. The purposes of this study are to analyze the flexural behaviour of the internal pre-stressed beams under the applied loading and to investigate and evaluate the use of finite element analysis of the pre-stressed concrete beams. Result showed that the flexural behaviour of the pre-stressed beam can be varied with the different applied loading and cracking also may be happened